Accuracy of Medial Tibiofemoral Joint Space Palpation Among Second- Year Doctor of Physical Therapy Students Using Ultrasound Verification: An Observational Study (International Journal of Physiotherapy, 2023)
Background: Palpation skills are universally taught in physical therapy education programs worldwide. Accurate palpation is necessary for diagnosis and to guide interventional approaches. The primary purpose of this investigation was to measure ultrasonographic-confirmed palpation accuracy of the medial tibiofemoral joint space among second year Doctor of Physical Therapy students examining participants with characteristics representative of patients seen in clinical practice.Methods: Five second-year Doctor of Physical Therapy students served as examiners. Thirty-six participants contributed 67 knees for examination. The primary outcome was ultrasonographic-confirmed palpation accuracy, and the secondary outcomes evaluated the association between palpation accuracy and participant characteristics.Results: Pooled examiner accuracy was 39%. Chi-Square analyses revealed no association between pooled examiner palpation accuracy and BMI category (x2=1.46, p=0.48), age category (x2=0.21, p=0.65), sex (x2=1.47, p=0.23), skin tone (x2=0.06, p=0.81), or side of the examined knee (x2=0.27, p=0.61). Individual examiner palpation accuracy ranged from 14% to 75%, revealing a significant difference across examiners (x2=15.0, p=0.005). Two examiners had a combined accuracy of 64%, while the remaining 3 had a combined accuracy of 24%. Chi-Square analyses revealed no association between "successful" vs "unsuccessful" examiners and BMI category (x2=3.54, p=0.17), age category (x2=1.39, p=0.24),sex (x2=4.22, p=0.04), skin tone (x2=0.001, p=0.97), or side of the examined knee (x2=0.08, p=0.77).Conclusion: This investigation provides original data of ultrasonographic-confirmed palpation accuracy among secondyear Doctor of Physical Therapy students examining participants with characteristics representative of patients seen in clinical practice. Results may help inform instructional approaches and curricular design in physical therapy education.